2015
DOI: 10.1016/j.cub.2015.10.059
|View full text |Cite|
|
Sign up to set email alerts
|

Chromatin

Abstract: Chromatin is a complex of proteins, RNA and DNA that constitutes the physiological state of the genome. Its basic structure is essentially the same in nearly all eukaryotes, from single-celled yeasts to the most complex multicellular organisms (exceptions include the chromatin of dinoflagellates and vertebrate sperm). Its fundamental role is to package the genome in a sufficiently compact form that allows comparatively very large molecules of DNA to fit inside the cell's nucleus. In human cells, the contour le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…These differences are likely to be partly due to the restricted site of interaction between plastic-bound NETs and the nearby partial surface of the islet versus the greater accessibility for free histones (in suspension) to interact with the entire islet surface. In addition, since there exists a 1:1 ratio of DNA to protein in chromatin ( 46 ), the histone content of PMA- and CI-NETs (with DNA content ≤ 1 μg /mL) was much lower than for free calf thymus histones (200–800 μg/mL), resulting in less toxicity for the islets. Nevertheless, this study demonstrated significant NET-induced toxicity for mouse islets in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…These differences are likely to be partly due to the restricted site of interaction between plastic-bound NETs and the nearby partial surface of the islet versus the greater accessibility for free histones (in suspension) to interact with the entire islet surface. In addition, since there exists a 1:1 ratio of DNA to protein in chromatin ( 46 ), the histone content of PMA- and CI-NETs (with DNA content ≤ 1 μg /mL) was much lower than for free calf thymus histones (200–800 μg/mL), resulting in less toxicity for the islets. Nevertheless, this study demonstrated significant NET-induced toxicity for mouse islets in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…The greater than twofold increase in transcription from a tandem duplicate could arise from aspects of various known regulatory mechanisms. Some of the possibilities we can envision include the following: (i) more frequent rebinding of transcription factors because the local concentration of binding sites is higher in tandemly arranged duplicates (18); (ii) more efficient looping of DNA due to clusters of transcription factors binding to identical sites on both gene copies (18); or (iii) more effective remodeling of chromatin to a favorable state for transcription (19). Any of these mechanisms could be enhanced or attenuated by neighboring sequences (i.e., by classical position effects), which could account for the observed dependence of the degree of overactivity on chromosomal position.…”
Section: The Biological Significance and Potential Mechanisms Underlyingmentioning
confidence: 99%
“…Histones, especially their N-terminal tails (containing an average of 15–30 residues), can undergo a plethora of PTMs, such as acetylation, methylation, phosphorylation, and more rarely, ubiquitination, sumoylation, and glycosylation [ 58 ]. The acetylation (ac) of histone lysines (K), is associated with the transition to an “open” conformation; this weakens DNA–histone interactions, increases DNA accessibility, and facilitates transcription.…”
Section: Epigenetics: Another Layer Of Information In Gene Expression Regulationmentioning
confidence: 99%